2014
DOI: 10.1016/j.jval.2014.08.2012
|View full text |Cite
|
Sign up to set email alerts
|

A Network Meta-Analysis Comparing the Efficacy And Safety of Ceftobiprole and Selected Comparators in the Treatment of Hospital-Acquired Pneumonia

Abstract: ber of exacerbations during the 6 month follow-up following initial exacerbation. We also compared health care utilization between both groups. Results: Among 115,489 infants (mean age: 13.9 months; 62.9% boys), 4,477 infants of the MTL-4 group were matched with 13,386 infants of the ICS group. In multivariate analysis, the risk of a new exacerbation was lower in infants of MTL-4 group compared to infants in ICS group (HR= 0.91, IC95% [0.87; 0.95]). The total number of exacerbations did not differ between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A retrospective study of the above RCTs evaluated the early clinical improvement in subgroups of high-risk patients. In some subgroups of high-risk patients with CAP (such as patients over 75 years old, or or CAP patients with COPD, or HAP patients with more than 10 baseline comorbidities), particular and significant results were observed that seemed to favor the ceftobiprole over comparators (Pooley et al, 2014).…”
Section: Antibiotics For Community Acquired Pneumoniamentioning
confidence: 99%
“…A retrospective study of the above RCTs evaluated the early clinical improvement in subgroups of high-risk patients. In some subgroups of high-risk patients with CAP (such as patients over 75 years old, or or CAP patients with COPD, or HAP patients with more than 10 baseline comorbidities), particular and significant results were observed that seemed to favor the ceftobiprole over comparators (Pooley et al, 2014).…”
Section: Antibiotics For Community Acquired Pneumoniamentioning
confidence: 99%